Analysis of Socio-economic Impacts of COVID-19 on Agricultural Practices Using Stepwise Regression - Manju Prem S.,; Mohanraj M.,; Sneha M. A.,; , Swadhin Priyadarsinee; Pooja Krishna J., (Archives of Current Research International, 2024)
The COVID-19 pandemic has profoundly impacted rural farming communities, revealing significant shifts in economic factors, production methods, and farm management practices. This study, conducted in Chikkaballapur district, Karnataka, delves into the socio-economic ramifications of the pandemic on agricultural practices and the livelihoods of farmers. Utilizing a stepwise regression analysis approach, the research identifies influential variables such as changes in farm management, production, and health and sanitation facilities. Data were collected from 50 respondents during the pandemic's peak, employing statistical measures like mean, standard deviation, and coefficient of variation for comprehensive analysis. The findings underscore the intricate relationships between various factors affecting rural livelihoods and highlight the need for targeted interventions and policy measures. The study emphasizes the critical need for tailored policy interventions to address the socio-economic impacts of COVID-19 on agricultural practices. Specifically, policy recommendations include enhancing access to agricultural extension services, promoting digital agricultural solutions, investing in healthcare infrastructure, supporting economic diversification, and strengthening social protection mechanisms. By aligning policy interventions with the findings and indicators observed in the research, policymakers can effectively support rural farming communities in navigating the challenges posed by the pandemic and building resilience for the future.